In vitro interactions of moroccan propolis phytochemical’s on human tumor cell lines and anti-inflammatory properties - Falcão, Soraia (2018)
Propolis is a resin manufactured by bees through the mixture of plant exudates and waxes with secreted substances from their metabolism, resulting in a complex mixture of natural substances of which quality depends on the phytogeographic and climatic conditions around the hive. The present study investigated the contribution of phenolic compounds to the cytotoxic and anti-inflammatory activities of propolis. The phenolic composition was evaluated by liquid chromatography with diode-array detection coupled to electrospray ionization tandem mass spectrometry (LC/DAD/ESI-MSn) analysis after phenolic extraction. The cytotoxicity of the extracts was checked using human tumor cell lines (MCF7- breast adenocarcinoma, NCI-H460- non-small cell lung carcinoma, HeLa- cervical carcinoma, HepG2- hepatocellular carcinoma, and MM127- malignant melanoma), as well as non-tumor cells (a porcine liver primary culture-PLP2). The anti-inflammatory activity was assessed using the murine macrophage (RAW 264.7) cell line. The results showed a composition rich in phenolic acids, such as ca eic and p-coumaric acid, as well as flavonoids, such as pinocembrin, pinobanksin, and pinobanksin-3-O-butyrate. Samples MP2 from Sefrou and MP3 from Moulay Yaâcoub presented a high concentration in phenolic compounds, while MP1 and MP4 from Boulemane and Immouzzer Mermoucha, respectively, showed similar composition with low bioactivity. The higher concentration of phenolic compound derivatives, which seems to be the most cytotoxic phenolic class, can explain the pronounced antitumor and anti-inflammatory activity observed for sample MP2.